Non-traditional financing in Algeria according to changes in the law of money and credit ... Is it a quantitative easing? - Remli, Hamza (Milev Journal of Research and Studies, 2018)
The aim of this study is to clarify the characteristics of unconventional financing according to the changes in the law of money and credit in Algeria, and to identify the most important changes in the financing of the public treasury by this type of financing. We also try to compare this policy with what is adopted in USA in the so-called quantitative easing. We have concluded that there is a significant difference between the two policies, mainly concentrated in the process of printing money in Algeria, while the process is considered as accounting records in the Federal Reserve's budget in the United States, and the difference in the conduct of the process and the mechanisms of closure.